Analisis Teori Konsumsi Islam terhadap Pola Konsumsi Siswa melalui Penggunaan Aplikasi SKOLA: (Studi Kasus Di SMK PGRI 13 Surabaya) - Purbayudha, Manida Niti (Institut Agama Islam YPBWI Surabaya, 2023)
The result showed that the consumption pattern of PGRI 13 Surabaya Vocational High School Students had implemented an attitude of not exaggerating, having sense of empathy so that students helped their fellow friends a lot by giving alms to food or giving money, applying adab ehen eating and drinking, always beig careful with halal labels and date expired save just in case Islamic consumption theory has also been applied by students through the SKOLA application with five principles, namely : the principles of justice, cleanliness, simplicity, generosity, and the principles of morality. The conclusion of this study is that based on the consumtion pattern they have used while using this application, a lot of awareness has been made and it reflects consumption behavior in Islam.